SYNTHESIS OF NANOCRYSTALS IN THE CORE/SHELL - Ishankulov Alisher Farmonovich (International Journal of Innovations in Engineering Research and Technology, 2021)
On the basis of a semiconductor material, a hybrid CdSe/ZnS quantum-sized (1-10 nm) hybrid of cadmium selenide with a “core-shell” structure was synthesized. The absorption and luminescence spectra of quantum dots were studied and quantum yield was calculated theoretically. The values of the theoretical and experimental dimensions of CdSe nanocrystals were studied comparatively. Optimal temperature conditions for efficient synthesis were determined.